Answer:
The general term of the sequence is
![{ - 1}^(n - 1)](https://img.qammunity.org/2021/formulas/mathematics/college/vressuqnlil9avg4fboaiy6qmoxif7ceoj.png)
Explanation:
The sequence above is a geometric sequence
For an nth term in a geometric sequence
![u(n) = a(r) ^(n - 1)](https://img.qammunity.org/2021/formulas/mathematics/college/2rvd20nmpoxez3713h15yz48d7da7hggsu.png)
Where n is the number of terms
a is the first term
r is the common ratio
From the above sequence
a = 1
r = -1/1 = -1
The nth term of the sequence is
![u(n) = 1 ({ - 1})^(n - 1) \\ = { - 1}^(n - 1)](https://img.qammunity.org/2021/formulas/mathematics/college/advw84xfrwosguwvrw05bpxc4w3f4rk4o3.png)
Hope this helps you